Amortization and Depreciation Methods in Bulgarian Industrial Enterprises – Possibilities and Solutions - Galabov, Marin (Research Papers, 2011)
This study deals with a number of issues referring to amortization and depreciation methods. Such methods significantly impact various aspects of economical activity in industrial firms. They are structured in two parts. The first part deals with amortization and depreciation and amortization and depreciation methods as interpreted by the legislation of Bulgaria and by the International Accounting Standards. The second part refers to the selection of amortization and depreciation methods for the specific purposes of the enterprise and the influence of these methods on the effectiveness on basis expenses and the profitableness on basis expenses. Besides, the research includes various tables and charts.This study is valuable for lecturers, students and experts working in the practice.